Exploring the ability of selected bacteria in potential naphthalene depletion and biosurfactant production - Muralikrishnan Veerasamy2, Munmun Sikdar1*, Santanu Das1, Dr. (Recent Research in Science and Technology, 2012)
Exploring the ability of selected bacteria in potential naphthalene depletion and biosurfactant production